Potential anti-aging effects of fermented wheat germ in aging mice. (August 2021) - Zhao, Yi; Liao, Ai-Mei; Liu, Na; Huang, Ji-Hong; Lv, Xing; Yang, Can-Rui; Chen, Wen-Jing; Hou, Yin-Chen; Ma, Li-Juan; Hui, Ming
Abstract: Fermented wheat germ (FWG) is a valuable food ingredient and is naturally rich in antioxidant components; fermentation can improve the antioxidant capacity of wheat germ. The complex anti-aging effect of WG is not fully understood. This study was carried out to explore the functional properties of FWG: BALB/c mice with d -galactose (D-gal; 300 mg/kg/d) induced aging were treated with FWG (20 mg/kg/d) for 6 wk. The control mice were compared to mice with D-gal induced aging and aging mice administered FWG. FWG increased organ indices and enhanced learning and memory. The amount of total cholesterol, triglycerides, and glucose in the serum of aging mice also decreased after supplementation with FWG. FWG intake enhanced antioxidant activity in aging mice. FWG significantly increased the levels of antioxidant enzymes, such as superoxide dismutase, glutathione peroxidase, and total antioxidant capacity; it decreased the level of malondialdehyde in different tissues, including the liver, brain, intestine and serum. High-throughput sequencing results showed that the ratio of Bacteroidetes to Firmicutes index and the number of beneficial bacteria in the FWG group increased, and the growth of pathogens was suppressed in the intestines. These results suggested that FWG holds a great potential as a functional food by reducing oxidative damage, maintaining the stability of intestinal bacteria, and delaying aging. Graphical abstract: Image 1